IMPROVEMENT OF PROFIT OR LOSS AND OTHER GENERALIZED INCOME STATEMENT: https://doi.org/10.5281/zenodo.15382511 - Safarov , Otabek (Journal of Contemporary World Studies, 2025)
In this article, Revenue includes all receipts, profits, and other benefits other than contributions from owners. Revenue is a component of income and arises from the sale of goods or services that are part of the ordinary activities of an entity. Transactions that are not part of the ordinary activities of an entity do not generate revenue. The gain on the sale of an intangible asset is not revenue. The fundamental principle of IFRS 15 is that revenue is recognized in the amount of consideration expected to be received in exchange for the goods or services promised to the customer.